2019
DOI: 10.1002/humu.23770
|View full text |Cite
|
Sign up to set email alerts
|

Novel missense mutation in VPS33B is associated with isolated low gamma‐glutamyltransferase cholestasis: Attenuated, incomplete phenotype of arthrogryposis, renal dysfunction, and cholestasis syndrome

Abstract: The typical phenotype of arthrogryposis, renal dysfunction, and cholestasis (ARC) syndrome involves three cardinal symptoms as the name describes, harboring biallelic mutations on VPS33B or VIPAS39. Except for ARC syndrome, low gammaglutamyltransferase (GGT) cholestasis often implies hereditary hepatopathy of different severity; however, some remain undiagnosed. Several monogenic defects typically with multiorgan manifestations may only present liver dysfunction at times, such as DGUOK defect and AGL defect. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
5
15
0
Order By: Relevance
“…Consequently, they were unable to fulfill their mission, i.e., to excrete bile acids, conjugated bilirubin, ALP, cholesterol, and other substances to the bile ducts [ 6 , 17 , 18 ]. In accordance with experimental findings and previously reported ARC patients, our patient developed elevated serum levels of conjugated bilirubin, bile acids, ALP, and triglycerides, and mildly elevated transaminases [ 8 , 10 12 , 19 23 ]. Normal of GGT is a constant finding in ARC-associated intrahepatic cholestasis and can be explained by the presence of normal bile ducts.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consequently, they were unable to fulfill their mission, i.e., to excrete bile acids, conjugated bilirubin, ALP, cholesterol, and other substances to the bile ducts [ 6 , 17 , 18 ]. In accordance with experimental findings and previously reported ARC patients, our patient developed elevated serum levels of conjugated bilirubin, bile acids, ALP, and triglycerides, and mildly elevated transaminases [ 8 , 10 12 , 19 23 ]. Normal of GGT is a constant finding in ARC-associated intrahepatic cholestasis and can be explained by the presence of normal bile ducts.…”
Section: Discussionsupporting
confidence: 93%
“…The stop-codon mRNA mediated decay of these mutations, although not proven, if present, should have a similar detrimental effect. The fact that a frame shift mutation in the report by Qiu et al [ 19 ] is considered pathogenic and the affected amino acid is located 137 amino-acids downstream in the protein sequence than the affected amino acid in the current case, greatly supporting the pathogenic nature of the mutation in our patient too. Smith et al [ 33 ] reported a single patient with failure to thrive, developmental delay, sensorineural hearing loss, renal loss of protein and amino acids, bilateral talipes with osteopenia, mild cholestasis, pruritus, and ichthyosis, but no arthrogryposis.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…One ARC patient was reported with high GGT cholestasis [63]. Recently, VPS33B variants were identified in patients that presented cholestasis but no other clinical features of classic ARC [64], underscoring a strong association between VPS33B and cholestasis.…”
Section: Vps33b and Vipas39mentioning
confidence: 98%